Society 5.0 - the role of the automotive industry - Stanojčić, Uroš; Stamenković, Dragan; Blagojević, Ivan; Popović, Vladimir (Industrija, 2023)
The simultaneous development and aging of society in Japan led to the idea of creating Society 5.0. The integration of physical and virtual space with the aim for the prosperity and safety of each individual represents the concept of the organization of society, which is called Society 5.0. In terms of mobility, which is one of the key areas in society organization, solutions are being explored to enable the use of autonomous vehicles and alternative transportation options. Additionally, advanced technologies in the automotive industry that focus on the needs of vehicle users and workers in the automotive industry are being specifically researched.